Cerebral Microcirculation, Perivascular Unit, and Glymphatic System: Role of Aquaporin-4 as the Gatekeeper for Water Homeostasis - Szczygielski, Jacek; Kopańska, Marta; Wysocka, Anna; Oertel, Joachim (Frontiers in Neurology, 2021)
In the past, water homeostasis of the brain was understood as a certain quantitative equilibrium of water content between intravascular, interstitial and intracellular spaces governed mostly by hydrostatic effects i.e. strictly by physical laws. The recent achievements of molecular bioscience has led to substantial changes in this regard. Some new concepts elaborate the idea that all compartments involved in cerebral fluid homeostasis create a functional continuum with an active and precise regulation of fluid exchange between them rather than only serving as separate fluid receptacles with mere passive diffusion mechanisms, based on hydrostatic pressure. According to these concepts, aquaporin-4 (AQP4) plays the central role in cerebral fluid homeostasis acting as a water channel protein. The AQP4 not only enable water permeability through the blood-brain barrier, but also regulates water exchange between perivascular spaces and the rest of the glymphatic system, described as pan-cerebral fluid pathway interlacing macroscopic cerebrospinal fluid (CSF) spaces with interstitial fluid of brain tissue. With regards to this, AQP4 makes water shift strongly dependent on active processes including changes in cerebral microcirculation and autoregulation of brain vessels capacity. In this paper, the role of the AQP-4 as the gatekeeper, regulating the water exchange between intracellular space, glymphatic system (including the so-called neurovascular units) and intravascular compartment is reviewed. In addition, the new concepts of brain edema as a misbalance in water homeostasis are critically appraised based on the newly described role of AQP-4 for fluid permeation. Finally, the relevance of these hypotheses for clinical conditions (including brain trauma and stroke) and for both new and old therapy concepts are analyzed.